Caracterização da demanda para o atendimento odontológico em duas unidades de urgência em Município do Interior de São Paulo - Flumignan, Jessica D. Pacheco (2014)
The guidelines of the National Oral Health Program established by the Brazilian Ministry of Health were a milestone to happen a restructuring of the oral healthcare in the country. That program determined that there was a network of primary care combined with all network services, ensuring integrality in actions, joining the individual to the collective, in the prevention, promotion, treatment and recovery of health of the population, not neglecting the necessary attention to the emergencies. The dental emergencies cover all immediate measures to relieve symptoms of pain, situations of infectious processes, trauma or even aesthetic. We have made a quantitative prospective study from a cross-section of the population to investigate the profile and characteristics of the demand for dentistry users treated at the Pre-Hospital Units (UPH) from the western and northern areas of the city of Sorocaba/SP. The analysis happened with an interview of 270 users in the period from 08 January to 21 February, 2013. The dentists who were acting with users in the period relating to interviews were also interviewed. The user s profile of this service was predominantly female (61.5% of the cases). The age group that s to od out was between 20-44 years old (68,2% females and 31,8% males). The complaint of pain was predominant, and may or may not be associated with another complaint. Most patients reported they knew about the UPH through their partners, but very close to this number we found reports of users who said they knew about it through their own UBS (Basic Health Units). The service of emergency care at the UPH showed 95.2% of interventions in the studied cases. We suggest some proposals aiming to qualify the service of the emergency department at the UPHs in Sorocaba